Social Media and Social Movements. Issue 9 (September 2016) - Kidd, Dustin; McIntosh, Keith
Abstract: What role does social media play in social movements and political unrest? Twitter, Facebook, Instagram, and Google have all been cited as important components in social revolutions, including those in Tunisia, Egypt, Iceland, Spain, and the global Occupy movement. This essay explores social science claims about the relationship between social networking and social movements. It examines research done on the relationship between social networking, the promotion of activism, and the offline participation in the streets. Can the technology of social networking help activists to achieve their goals? If so, is it just one of many tools they may use, or is the technology so powerful that the right use will actually tip the scales in favor of the social movement? This scholarship divides into optimistic, pessimistic, and ambivalent approaches, turning on an oft‐repeated question: will the revolution be tweeted?